The impact of non-financial rewards orientated HRM practices on employee's performance in public and private Health sectors in Sulaimani City - Mohammed Jalal Mohammed Ameen; Abbas Ali karem; Nozad Hussein Mahmood (مجلة الغري للعلوم الاقتصادية والادارية)
Acknowledging the importance of employee motivation beyond financial incentives, this research examines the understudied impact of non-financial rewards (NFRs) in the Sulaimani city healthcare system. The primary objective was to assess the influence of specific NFRs  namely recognition, feedback, and work-life balance on employee performance in the public and private health sectors within Sulaimani City. A quantitative methodology was adopted, utilizing a structured questionnaire featuring fourteen 5-points Likert-scale items as the primary data collection tool to measure the core variables. Data were gathered from a sample of 70 employees distributed across two public (Shar and General) and two private (Farwq and Anwar Shekha) hospitals in Sulaimani City. Statistical analysis, including correlation and multiple linear regression performed via SPSS Version 27 and JMP-Pro Version 17, revealed that recognition, feedback, and work-life balance all significantly and positively enhance employee performance. Feedback demonstrated the strongest association, followed by recognition, and then work-life balance. The research adds to the body of knowledge about the importance of non-financial motivational schemes to employees’ performance improvement in Iraq. Such findings clearly provide evidence that health sector organizations in the country and perhaps in practically other contexts should adopt and have robust non-financial reward systems to ensure the performance of their employees.